Factors that Undermine Service Delivery by Civil Engineers in South African Local Municipalities - Zeleke Bekele Worku; Reginald Legoabe (Salehan Institute of Higher Education, 2017)
The objective of study was to identify and quantify key predictors of job satisfaction among civil engineers working in South African local municipalities. The design of study was cross-sectional, descriptive and evaluative. The study was conducted against the background of shortage of suitably qualified, adequately motivated and skilled civil engineers working in local municipalities. The degree of job satisfaction of respondents was assessed by using a composite index developed by Turkyilmaz, Akman, Ozkan and Pastuszak (2011) for conducting a similar study. A combination of quantitative and qualitative methods of data collection and analyses were used in the study. As part of the quantitative aspect of study, data was collected from a stratified random sample of size 250 civil engineers working in various South African local municipalities. As part of the qualitative aspect of study, individual in-depth interviews were conducted with 37 civil engineers working in various local municipalities. Four focus group interviews were conducted as part of the study. Data was collected by using a structured, pretested and validated questionnaire of study. Quantitative data analyses were conducted by using methods such as frequency tables, cross-tab analyses (Pearson’s chi-square tests of associations) and binary logistic regression analysis. The results showed that 171 of the 250 respondents who took part in the study (68.40%) were satisfied with the job that they were performing in the various local municipalities, whereas the remaining 79 of the 250 respondents in the study (31.60%) were not satisfied with their jobs. Based on results obtained from cross-tab analyses at the 5% level of significance, the degree of job satisfaction of civil engineers at the workplace was significantly and adversely affected by too much workload, poor working conditions, lack of budget for construction projects, low salary and remuneration, lack of training opportunities, lack of cooperation and appreciation, too much bureaucracy and red tape, short duration of service, and poor relationship with supervisors, in a decreasing order of strength. Results obtained from binary logistic regression analysis showed that the degree of job satisfaction of civil engineers at the workplace was significantly and adversely affected by 3 factors. These 3 factors were too much workload, poor working conditions, and lack of budget for construction projects in a decreasing order of strength. Results obtained from individual and focus group in-depth interviews led to similar findings.